Measuring health-related stigma: Exploring challenges and research priorities to improve assessment - Marente M. Mol; Marlies J. Visser; Sarju S. Rai; Ruth M. H. Peters (Taylor & Francis Group, 2023)
Despite the advances in stigma research, measuring health-related stigma continues to be challenging and knowledge gaps remain. This study gained insight into challenges and research priorities related to the assessment of health-related stigma. Interviews were conducted with 14 stigma researchers, followed by a survey that was completed by 36 respondents. The findings showed a diverse range of research priorities. Among the top ranked priorities were the need for robust measurement properties of existing scales (content validity, responsiveness, validation across settings), exploration and assessment of subtle changes in stigma, and investigation on ways to assess actual behaviour and discrimination. Various challenges with the cross-cultural use of measures were identified, along with a research opportunity to shorten the cross-cultural validation process. Other identified research priorities related to: studying multi-level intersectional stigma; focusing on positive features that counter stigma; rephrasing negative and offending scale items; developing generic measures; and, the further development of practical tools to support researchers with scale implementation. The defined research priorities can guide future studies to advance stigma measurements and, as our ability to measure is critical for our understanding, enhance our knowledge about the complex stigma processes.